Repair welding of ductile cast iron by laser cladding process: microstructure and mechanical properties. (December 2014) - Lin, C.-M.; Chandra, A. S.; Morales-Rivas, L.; Huang, S.-Y.; Wu, H.-C.; Wu, Y.-E.; Tsai, H.-L.
Abstract : The aim of this research was to determine the feasibility of a newly developed process in the repair of cracked gas turbine casings made of ductile cast iron. This study investigated the microstructural characteristics, metallurgy and mechanical properties of the repair weldments produced using fibre laser cladding. Optical microscopy, scanning electron microscopy and element probe microanalysis were used to investigate the microstructure at the cladding weld interface. The mechanical properties of the cladded specimens were evaluated after laser cladding. Our results revealed that the weldability of ductile cast iron can be enhanced by performing laser surface pretreatment to sublimate graphite nodules. Microhardness at the interface of the laser cladded weldments depended largely on the range of the heat affected zone and the degree of phase complexity. Under tensile loading, failures were limited to the base metal region of the weldments. Test results demonstrate that the impact toughness of the interface between the fusion zone and the base metal can be enhanced through the application of post-cladding heat treatment.